Studi Konsentrasi Amiloglukosidase dan Saccharomyces cereviseae dalam Produksi Bioetanol dari Ubi Jalar Melalui Sakarifikasi Fermentasi Simultan - Bambang Admadi Harsojuwono (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2015)
The purpose of this study is to obtain the enzyme concentration and Sacharomyces cereviceae amyloglukosidase best to process simultaneous saccharification fermentation (SFS) in the production of bio ethanol from sweet potato hydrolyzated. This study was designed using a factorial randomized block design. The first factor is the concentration of enzyme amiloglukosidase consisting of 3 levels ie 0.8; 1.0 and 1.2 ml / kg substrate. The second factor is the concentration of S. cereviceae consisting of 3 levels ie 5; 10 and 15% (v / v). Variable measured include of ethanol concentration, yield, efficiency of substrates using, fermentation efficiency and concentration of substrate consumption. Data were analyzed diversity and Duncan's multiple comparison test was done to determine the best treatment. The results showed that the concentration of the enzyme amyloglukosidase 1.2 ml / kg of substrate (3000 U / ml) at a concentration of S. cereviceae 10% (v / v) is the best treatment with the resulting ethanol concentration 7.48% (v / v), yield 19.89%, the efficiency of product formation by substrate 47.37%, 92.88% fermentation efficiency, and the concentration of substrate consumption of 15.78 g / L.